Online Child Sexual Exploitation And Abuse As Organized Crime: Towards a New International Legal Framework - Septianita, Hesti; Pujiyono; Cahyaningtyas, Irma (LITIGASI, 2026)
Online child sexual exploitation and abuse (OCSEA) has developed as an important manifestation of transnational organized crime, constituting a systematic violation of children's fundamental rights under international law. This study considers the structural transformation of OCSEA — starting from local, offline incidents to coordinated darknet operations characterized by hierarchical criminal networks, role specialization, cryptocurrency-based financial flows, and cross-border coordination. Employing a doctrinal legal approach, blended with comparative jurisdictional analysis and concrete review of law enforcement data, this research carefully evaluates the capacity of existing international legal regimes to address OCSEA as organized crime. The analysis shows substantial normative and institutional deficiencies across key international instruments — including UNTOC, the Optional Protocol to the Convention on the Rights of the Child, the Budapest Convention on Cybercrime, the Lanzarote Convention, and relevant ASEAN frameworks — encompassing definitional inconsistencies, fragmented jurisdictional authority, inadequately harmonized criminal standards, and enforcement gaps that organized criminal networks systematically exploit. The study further shows that OCSEA satisfies the defining criteria of transnational organized crime, as offenders across multiple jurisdictions collaborate in the production, distribution, and financial exploitation of child sexual abuse material (CSAM) through advanced technical infrastructure. Accordingly, this research develops a normative argument for a binding global legal framework that standardizes criminal definitions, establishes universal jurisdiction, strengthens cross-border cooperation, and institutionalizes international monitoring. In doing so, it contributes theoretically by reconceptualizing OCSEA within the transnational organized crime paradigm, and normatively by proposing a coherent direction for international legal reform.